2022
DOI: 10.1111/aec.13243
|View full text |Cite
|
Sign up to set email alerts
|

The living dead: Demography of Australian sandalwood in Australia's western rangelands

Abstract: One-third of the world's trees are at risk of extinction, with large, old, long-lived trees among the most vulnerable. Long-lived trees in arid and semi-arid biomes are particularly at risk, including Australian sandalwood (Santalum spicatum, Santalaceae), which is experiencing substantial population decline due to a suite of natural and anthropogenic drivers, with no appreciable recruitment estimated for more than 80 years. To contextualize this range-wide collapse and quantify regional variation in populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…However, the dominant tree species, Senegalia nigrescens , did have a tree loss post‐drought where elephants were present. In Western Australia, McLellan and Watson (2022) assessed sandalwood ( Santalum spicatum ) population age structure across a 1500 km arc in the western rangelands. The demography assessment found that sandalwood populations are declining with most trees in a state of senescence and few, if any, of the seedlings expecting to survive to maturity.…”
mentioning
confidence: 99%
“…However, the dominant tree species, Senegalia nigrescens , did have a tree loss post‐drought where elephants were present. In Western Australia, McLellan and Watson (2022) assessed sandalwood ( Santalum spicatum ) population age structure across a 1500 km arc in the western rangelands. The demography assessment found that sandalwood populations are declining with most trees in a state of senescence and few, if any, of the seedlings expecting to survive to maturity.…”
mentioning
confidence: 99%